GENETIC SOURCES AND MECHANISM OF MOLECULAR EVOLUTION OF THE A/HINI - 2009 INFLUENZA VIRUS CAUSING GLOBAL PANDEMIC IN HUMAN - Hoà, Lê Thanh (Vietnam Journal of Biotechnology, 2011)
Influenza A viras is well known as a special entity of undergoing multiple evolutionary process to gain its capability  for  genetic changes  to form  novel  lineage(s)/subtype(s)  either through  mutation,  'antigen drift'  or reassortment,  'antigen  shift'.  Antigen  shift  is  a  process  of  exchanging  genetic  materials  derived  from reassortment  of  gene  segments  between  virases,  within  and  between  subtypes,  resulting  in  an  antigenically novel viras that is capable of causing a worldwide pandemic. The novel A/HINI  - 2009 (A/(HlNl)v;  S-OIV) currently  causing  global  pandemic  is  a-remarkable representative  for  such  reassortment  within  and  between lineages/subtype(s)  of  the  influenza  A  viruses.  A  serial  lineages  and  subtj^es  of  influenza  A  causing pandemics in the 20* century and the present HlNl  (2009), are examples as consesquences ofthe  evolutionary process  of  reassortment  from  many  influenza  A  lineages/sublineages  of  human  and  animal  origins.  Among them, there have been encountered the lineages/subtypes: i) the HlNl  which caused the Spanish flu pandemic in  1918; ii) the H2N2 which  caused the Asian flu pandemic  in  1957 -  1958; iii) the H3N2 which  caused the Hongkong flu pandemic in 1968 - 1969; and iv) the novel HlNl  reassortant which is causing the current 2009 pandemic.  The  A/HlNl   -  2009  influenza   lineage  genetically,  antigentically  and  pathogenically   differs completely from the previous HlNl  lineages; it is a human HlNl  to be formed through a number of evolution stages from many genetic sources and lineages ofthe  influenza viras. This is the resulting reassortant of either antigen drift  and antigen shift  (reassortment) from many  swine, human and avian lineages of North American and Eurasian origins. The polymerase PB2 and PA were obtained from the H3N2 swine genetic source which previously reasserted from the North American avian and swine influenza;  the PBl  typically from  the human A/H3N2;  the  hemagglutinin  HA(Hl),  nucleoprotein  NP  and  non-stractural  NS  collected  from  the  classical swine  HlNl   and  H3N2;  the  NA(N1)  and  M  obtained  from  the  Eurasian  H1N1/H3N2  Imeage  of  swine influenza. All the segments to constract the HlNl  - 2009 have undergone multiple genetic variations compared to the previous genetic sources, particularly, hemagglutinin HA(Hl) differs  about 28% in terms of nucleotide and  amino  acid  of  HAj  and  different  glycosylation  sites  from  the  HA  of  H1N1(1918)  and  H1N1(2008). Likewise, the NA(N1) of  A/HINI  - 2009 has such high level of variation. Vietnam is currently one of nearly 150  nations  confronting  HlNl   -  2009  pandemic  and  the  infection   wave  spreads  rapidly  to  many  of cities/provinces. In this review, we are presenting informative data about the genetic sources and mechanism of molecular evolution to form  the current human A/HINI  - 2009, particularly,  detailing  its emergence history, circulation,  general  characteristics  of  evolution;  mechanism  of  the  viralence  and  genetic  changing  process; several  features  of  measurement  and  prevention  to  be  implemented.  The  emergence  and  circulation  of  the  human  A/HINI  -  2009  in  Vietnam  poses  the  potential  threat  and  high  presure  on  us  to  confront  a  new influenza  epidemiology  in  our  country,  in  paralell  with  the  H5N1  avian  influenza  circulating  during  many years now.